SAT0075 The use of macrophage mannose receptor-targeting nanobodies and spect imaging to study joint inflammation in mice with collagen-induced arthritis. (23rd January 2014) - Put, S.; Schoonooghe, S.; Devoogdt, N.; Schurgers, E.; Avau, A.; Mitera, T.; De Baetselier, P.; Raes, G.; Lahoutte, T.; Matthys, P.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that occurs in 0.5-1.0% of the population worldwide. The primary affected organ is the small diarthrodial joint, where the synovial membrane, cartilage and bone tissue will be damaged, ultimately leading to joint deformity and disability of the patient. In the pathogenesis of RA, the synovial membrane becomes hyperplastic and will be infiltrated with T cells, B cells, neutrophils and macrophages. A hallmark of RA is the progressive destruction of bone tissue caused by an elevated bone resorption by osteoclasts, multinuclear cells derived from the monocyte/macrophage lineage. Objectives: Our goal was to provide a method to visualize and quantify joint inflammation by the use of an animal model of RA, namely collagen-induced arthritis (CIA). We focused on the macrophage mannose receptor (MMR), since this protein is a well described marker for macrophages, which are numerously present in inflamed tissues. Methods: CIA was induced in DBA/1 mice by the injection of collagen type II in Complete Freund's adjuvant. Flow cytometry and qPCR were used to study the expression of MMR in vitro in macrophages and osteoclasts and in vivo in CIA. SPECT/CT imaging with 99m Tc-labeled nanobodies generated against MMR was performed to visualize and quantify MMR expression in the joints of mice. Results: MMR expression was shown to be highly upregulated in cultures of bone marrow-derived macrophages and osteoclasts by qPCR and by flow cytometry using MMR-targeting nanobodies. Ex vivo, we identified MMR in lymph nodes, spleen and bone marrow of naïve and arthritic mice. Interestingly, we detected expression of MMR in the synovial fluid, and to a lesser extent in synovium, of mice with CIA. More specifically, MMR was present on CD11b + F4/80 + macrophages isolated from the synovial fluid of the inflamed joints. SPECT/CT imaging was used to detect MMR in vivo in mice with CIA. Therefore, nanobodies against MMR were radioactively labeled with 99m Tc, while nanobodies targeting a bacterial enzyme were used as controls. We observed high signals of MMR in lymph nodes, spleen and liver in naïve conditions as well as after immunization. Importantly, the joints of arthritic mice displayed high retention of MMR nanobody. The signal from SPECT imaging was significantly higher in mice with arthritic symptoms compared to naïve animals or immunized mice without clinical symptoms. Conclusions: The use of MMR nanobodies in SPECT/CT imaging generates the possibility to track and quantify inflammatory macrophages in vivo in arthritic joints. In vivo quantification of joint inflammation by non-invasive techniques would be a great help in diagnosis and monitoring of disease processes as well as testing the efficiency of (new) drugs. Disclosure of Interest: None Declared